PENERAPAN KENDALI JARINGAN NEURAL PADA SISTEM GERAKAN LURUS PRESISI - Santoso, Ilham Budi; Abidin, Zainal (Mesin, 1999)
This paper presents an empirical result on the application of neural network controller in a precision straight motion system. As a controller, neural networks learn in two phase. In the ï¬rst learning phase, neural network was doing inverse system identification. It is called general learning. In the second learning phase, neural network was applied as an adaptif controller which doing online learning. It is ca//ed special learning. Through these two learning phases, neural network shows a good performance for wide range operation with a minimum operator/human intervention.